A Two-Decade Review of Teaching and Learning in Education for Sustainable Development - Wardani, Duhita Savira; Widodo, Ari; Syaodih, Ernawulan; Muslim, Muslim (IJORER : International Journal of Recent Educational Research, 2026)
This research seeks to present a comprehensive depiction of scholarly developments in the field of teaching and learning within Education for Sustainable Development (ESD) by examining patterns of scientific productivity, dominant publication outlets, as well as the most active authors, countries, and their collaborative networks. Data were obtained through the extraction of relevant articles from the Scopus online database in November 2023. A total of 490 Scopus-indexed publications produced over a twenty-year period (2003–2023) were identified and selected for bibliometric analysis. The retrieved records were exported in BibTeX format and subsequently transformed into a data frame using functions available in the bibliometrix package. The results reveal a steady and notable growth in research output related to teaching and learning on ESD throughout the past two decades. In addition, the analysis highlights a shift in research emphasis: earlier studies tended to focus more broadly on ESD discourse, whereas more recent publications demonstrate increasing attention toward empirical investigations specifically addressing teaching and learning practices within the ESD context. Unlike existing ESD bibliometric studies that emphasize general thematic development, this review uniquely foregrounds the evolution of teaching and learning research within ESD. The fundamental finding reveals a clear longitudinal shift from conceptual discourse toward empirically driven pedagogical research, indicating the maturation of ESD as an evidence-based educational field.